2014
DOI: 10.1016/j.ijcard.2014.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with the PCSK9 inhibitor alirocumab versus ezetimibe in patients with hypercholesterolemia: Results of a 24week, double-blind, randomized Phase 3 trial

Abstract: Alirocumab demonstrated significantly greater LDL-C lowering versus ezetimibe after 24 weeks with the lower 75 mg Q2W dose sufficient to provide ≥ 50% LDL-C reduction in the majority of the patients. Adverse events were comparable between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 22 publications
9
189
0
5
Order By: Relevance
“…A total of 138 study arms from 35 studies were analyzed, comprising 45 539 patients (Table S1). 5, 11, 12, 13, 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43 Alirocumab was used in 18 studies (28 treatment arms), and evolocumab was used in 17 studies (39 treatment arms; Figure 1); placebo was the most common control used (52 control arms), with ezetimibe used in 17 arms, and standard therapy in 2 arms. Eight studies were of an exclusively FH population, and 5 studies included only patients intolerant to statins.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 138 study arms from 35 studies were analyzed, comprising 45 539 patients (Table S1). 5, 11, 12, 13, 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43 Alirocumab was used in 18 studies (28 treatment arms), and evolocumab was used in 17 studies (39 treatment arms; Figure 1); placebo was the most common control used (52 control arms), with ezetimibe used in 17 arms, and standard therapy in 2 arms. Eight studies were of an exclusively FH population, and 5 studies included only patients intolerant to statins.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the design of each of these studies have been reported previously (Figure 1). 13, 14, 15, 16, 17, 18, 19, 20, 21 The data, analytic methods, and study materials for this secondary analysis will not be made available to other researchers for purposes of reproducing the results or replicating the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Alirocumab, a fully human monoclonal antibody that specifically binds to PCSK9, has been shown to significantly lower LDL‐C levels across a range of dosing regimens, whether as monotherapy12 or on a background of statin±other lipid‐lowering therapies 13, 14, 15, 16. A monthly dosing regimen may be convenient and effective,17, 18 with different doses being appropriate when used as monotherapy compared with background statin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This study also employed an alirocumab dosing regimen of 75 mg every 2 weeks (Q2W; with possible dose adjustment to 150 mg Q2W; referred to as “75Q2W”) as a calibrator arm, a dose that has been extensively investigated across the phase 3 ODYSSEY clinical trials program 12, 13, 14, 15, 16. CHOICE II followed a “treat‐to‐target” dosing strategy, based on the LDL‐C reduction needed to provide best achievement of target LDL‐C level at the lowest alirocumab dose.…”
Section: Introductionmentioning
confidence: 99%